Access Granted? An Examination of Financial Capability, Trait Hope, Perceived Access, and Food Insecurity in Distressed Census Tracts. Issue 2 (April 2020) - Gilbert, Jonathan Ross; Ashley, Christy
Food insecurity and poor nutrition negatively affect consumer health and well-being. Trait hope is conceptualized as a powerful thought process that can facilitate change. However, it is unclear how trait hope, the sense that one can successfully plan and put forth energy to meet goals, influences food insecurity among impoverished consumers. The authors conducted an evaluative study using in-home surveys (n = 498) in seven distressed census tracts of a midsized southeastern U.S. city to understand how financial capability and trait hope, a cognitive process, interact to influence perceived access to fresh food among Black and Hispanic consumers that disproportionately face food insecurity. Trait hope positively moderated the relationship between financial capability and perceived access, which was related to lower food insecurity. The results, which indicated important differences related to race/ethnicity, suggest that interventions that improve financial capability and increase trait hope may improve efficacy of food and nutrition assistance programs.